Increased amounts of cell-free DNA released from a culture with a high content of cancer stem cells - Fernández-Domínguez, Ileana J.; Pérez-Cárdenas, Enrique; Taja-Chayeb, Lucia; Wegman-Ostrosky, Talia; Caro-Sánchez, Claudia H. S.; Zentella-Dehesa, Alejandro; Dueñas-González, Alfonso; López-Basabe, Horacio; Morales-Bárcenas, Rocío; Trejo-Becerril, Catalina (Frontiers in Cell and Developmental Biology, 2025)
BackgroundThe study and characterization of cell-free DNA (cfDNA) has gained significant importance due to its clinical applications as a diagnostic and prognostic marker. However, it remains unclear whether all cell populations within a tumor or culture contribute equally to its release. This pioneering research analyzes the contribution of cancer stem cells (CSCs) in colon cancer cell lines to the amount of cfDNA released and its role in cellular transformation.MethodsThe CSC population derived from the SW480 colon cancer cell line was enriched using a non-adhesive culture system to assess the quantity and electrophoretic profile of the released cfDNA. Subsequently, in vitro transformation assays were conducted to compare the transforming capacity of the cfDNA obtained from enriched cultures with that from non-enriched cultures. Group differences were analyzed using analysis of variance (ANOVA), followed by post hoc interpretation with Tukey’s test.ResultsOur study revealed that cultures with CSCs released greater amounts of cfDNA, displaying a distinct fragment profile. Additionally, cfDNA from different cellular origins influenced the transformation characteristics of NIH3T3 cells. This is the first demonstration of a link between CSC proportions and cfDNA release, suggesting that CSCs and microenvironmental conditions can affect cfDNA quantity and its potential to induce transformation.ConclusionThese findings highlight the importance of cfDNA in carcinogenesis and its potential as a biomarker and therapeutic target, especially given the role of CSCs in drug resistance and tumor aggressiveness.